Training objectives and importance of multicultural assessment development for guidance and counseling teachers in Karanganyar - Agus Basuki; Fadhila Malasari Ardini; Ismarini Bekti Setiani; Sesya Dias Mumpuni (Community Empowerment, 2024)
This training aimed to improve Karanganyar Middle School guidance and counseling (BK) teachers' ability to develop and implement culturally sensitive multicultural assessments. The program used a training methodology incorporating lectures, discussions, brainstorming, and experience sharing. Karanganyar Regency BK teachers already possessed some experience with multicultural assessments. Wilcoxon test results (p = 0.000< 0.05) showed a significant difference between pre- and post-test scores, with significantly higher post-test scores (average positive mean rank: 12.95; average negative mean rank: lower). Therefore, the training was effective in enhancing Karanganyar Middle School BK teachers' understanding, skills, and knowledge of multicultural assessments.